The Diapause Lipidomes of Three Closely Related Beetle Species Reveal Mechanisms for Tolerating Energetic and Cold Stress in High-Latitude Seasonal Environments - Lehmann, Philipp; Westberg, Melissa; Tang, Patrik; Lindström, Leena; Käkelä, Reijo (Frontiers in Physiology, 2020)
During winter insects face energetic stress driven by lack of food, and thermal stress due to sub-optimal and even lethal temperatures. To survive, most insects living in seasonal environments such as high latitudes, enter diapause, a deep resting stage characterized by a cessation of development, metabolic suppression and increased stress tolerance. The current study explores physiological adaptations related to diapause in three beetle species at high latitudes in Europe. From an ecological perspective, the comparison is interesting since one species (Leptinotarsa decemlineata) is an invasive pest that has recently expanded its range into northern Europe, where a retardation in range expansion is seen. By comparing its physiological toolkit to that of two closely related native beetles (Agelastica alni and Chrysolina polita) with similar overwintering ecology and collected from similar latitude, we can study if harsh winters might be constraining further expansion. Our results suggest all species suppress metabolism during diapause and build large lipid stores before diapause, which then are used sparingly. In all species diapause is associated with temporal shifts in storage and membrane lipid profiles, mostly in accordance with the homeoviscous adaptation hypothesis, stating that low temperatures necessitates acclimation responses that increase fluidity of storage lipids, allowing their enzymatic hydrolysis, and ensuring integral protein functions. Overall, the two native species had similar lipidomic profiles when compared to the invasive species, but all species showed specific shifts in their lipid profiles after entering diapause. Taken together, all three species show adaptations that improve energy saving and storage and membrane lipid fluidity during overwintering diapause. While the three species differed in the specific strategies used to increase lipid viscosity, the two native beetle species showed a more canalized lipidomic response, than the recent invader. Since close relatives with similar winter ecology can have different winter ecophysiology, extrapolations among species should be done with care. Still, range expansion of the recent invader into high latitude habitats might indeed be retarded by lack of physiological tools to manage especially thermal stress during winter, but conversely species adapted to long cold winters may face these stressors as a consequence of ongoing climate warming.